Quantitative Immunoexpression of EGFR in Oral Potentially Malignant Disorders: Oral Leukoplakia and Oral Submucous Fibrosis - Naga Jyothi Meka; Sridevi Ugrappa; Nagalaxmi Velpula; Sravan Kumar; Kotya Naik Maloth; Srikanth Kodangal; Lalitha ch; Stuti Goyal (Tabriz University of Medical Sciences, 2015)
Background and aims. Many oral squamous cell carcinomas develop from potentially malignant disorders (PMDs)which include a variety of lesions and conditions characterized by an increased risk for malignant transformation. Thisstudy evaluated the quantitative expression of EGFR in normal oral mucosa, oral leukoplakia and oral submucous fibrosis to predict the malignant risk in compliance with the intensity of staining with EGFR. Materials and methods. Thirty subjects were included in the study, consisting of 10 oral leukoplakia (OL), 10 oral sub-mucous fibrosis (OSMF) and 10 normal oral mucosa (NOM) as the control group. Owing to the histopathological confirma-tion of precancerous state of tissue, 4-μm-thick sections of tissue were taken from paraffin-embedded wax blocks for im-munohistochemical staining for EGFR. Results. All the control cases showed positive expression for EGFR, while 20% of oral leukoplakia and 40% of OSMF cases showed strong expression (3+), 40% of OL and 30% of OSMF cases showed weak expression (2+), and 40% of OLand 30% of OSMF cases showed poor expression (1+) compared to controls (P=0.012). Conclusion. EGFR expression levels in the premalignant lesion appear to be a sensitive factor in predicting the neoplastic potential. This suggests that EGFR may serve as a biological marker to identify high-risk subgroups and guide prophylactic therapy with chemopreventive drugs or surgical intervention to prevent progression to carcinoma. Hence, further investiga-tions in the direction of chemopreventive trials with a larger sample size are suggested to determine its role in the head and neck tumorigenesis.